The efficacy of first and second immunotherapy exposure in patients with recurrent or metastatic cervical cancer - Mingxiu Ju; Baoyue Pan; Yongwen Huang; Yun Zhou; Jieping Chen; Huiling Xiang; Shije Xu; Siyu Chen; Chunyan Lan; Jundong Li; Min Zheng (Cancer Medicine)
Abstract Objective Immunotherapy has led to changes in cervical cancer guidelines. Therefore, additional biomarkers to identify the ideal patient who would experience the most benefit may be important. Methods We retrospectively collected 208 patients with R/M CC and recorded clinicopathologic information, peripheral blood markers and treatments to analyze the prognostic factors of clinical outcomes. Response rate comparison, univariate, and multivariate analyses were performed to assess the efficacy of different factors. Results A total of 43.27% patients achieved objective responses, including 18 with complete response and 72 with partial response. Patients receiving first‐line immunotherapy had much higher objective response rate (ORR) than the remaining patients (53.8% vs. 34.8%, p = 0.006). CRP >3 ECOG ≥1 and recurrence in 6 months predicted shorter progression free survival (PFS). CRP >3, GLU >6.1 independently predicted unfavorable overall survival (OS). Compared with no antiangiogenic therapy, previous antiangiogenic therapy reduced the median OS by nearly 14 months. Immunotherapy rechallenge was still effective after first immunotherapy failure, and combined with dual‐immunotherapy or bevacizumab combined with chemoradiotherapy resulted in a 60.00% or 62.50% ORR, respectively. Patients with squamous cell carcinoma, with stable disease or objective response in the first immunotherapy or without chemotherapy in second immunotherapy had favorable clinical outcome. Conclusion The baseline CRP levels in serum was an independent factor for PFS and OS of R/M CC patients treated with immunotherapy, and previous antiangiogenic therapy was associated with poor OS. Patients still show response to immunotherapy rechallenge and combined treatment with bevacizumab or candonilimab showed higher response rate than anti‐PD‐1 after immunotherapy failure.